The Lake Shore Limited - Miller, Sue, 1943- (Alfred A. Knopf, 2010)
"The Lake Shore Limited" is the story of how Wilhelmina "Billy" Gertz has come to create the title's play out of emotions surrounding an imagined terrorist bombing of a Chicago train, how the play is then created anew on the stage, and how the play's performance touches and changes the lives that intersect and interweave with Billy's.